Algebra-Lineares Gleichungssystem-Einsetzverfahren (2)
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
Beispiel Nr: 25
$\begin{array}{l}
\text{Gegeben:} \\
a1 \cdot x +b1 \cdot y =c1\\
a2 \cdot x +b2 \cdot y =c2 \\
\\ \text{Gesucht:} \\\text{x und y}
\\ \\ \textbf{Gegeben:} \\
\\
3x +6y =8\\
9x +0y = 9 \\
\\
\\ \\ \textbf{Rechnung:} \\\begin{array}{l|l}
\begin{array}{l}
I \qquad 3 x +6 y =8\\
II \qquad 9 x +0 y = 9 \\
\text{I nach x auflösen}\\
3 x +6 y =8 \\
3 x +6 y =8 \qquad /-6 y\\
3 x =8 -6 y \qquad /:3 \\
x =2\frac{2}{3} -2 y \\
\text{I in II}\\
9 (2\frac{2}{3} -2 y ) + 0 y = 9 \\
24 -18 y +0 y = 9 \qquad / -24 \\
-18 y +0 y = 9 -24 \\
-18 y = -15 \qquad /:\left(-18\right) \\
y = \frac{-15}{-18} \\
y=\frac{5}{6} \\
x =2\frac{2}{3} -2 y \\
x =2\frac{2}{3} -2 \cdot \frac{5}{6} \\
x=1 \\
L=\{1/\frac{5}{6}\}
\end{array} &
\begin{array}{l}
I \qquad 3 x +6 y =8\\
II \qquad 9 x +0 y = 9 \\
\text{I nach y auflösen}\\
3 x +6 y =8 \\
3 x +6 y =8 \qquad /-3 x\\
6 y =8 -3x \qquad /:6 \\
y =1\frac{1}{3} -\frac{1}{2}x \\
\text{I in II}\\
9x + 0(1\frac{1}{3} -\frac{1}{2} x ) = 9 \\
0 -0 x +0 x = 9 \qquad / -0 \\
-0 x +0 x = 9 -0 \\
9 x = 9 \qquad /:9 \\
x = \frac{9}{9} \\
x=1 \\
y =1\frac{1}{3} -\frac{1}{2} x \\
y =1\frac{1}{3} -\frac{1}{2} \cdot 1 \\
y=\frac{5}{6} \\
L=\{1/\frac{5}{6}\}
\end{array}
\end{array}
\end{array}$